2014
DOI: 10.1002/acr.22405
|View full text |Cite
|
Sign up to set email alerts
|

Early Progressive Strength Training to Enhance Recovery After Fast‐Track Total Knee Arthroplasty: A Randomized Controlled Trial

Abstract: Objective. To compare 7 weeks of supervised physical rehabilitation with or without progressive strength training (PST) commenced early after fast-track total knee arthroplasty (TKA) on functional performance. Methods. In total, 82 patients with a unilateral primary TKA were randomized to 2 different interventions: 7 weeks of supervised physical rehabilitation with PST (PST group) and without PST (CON group) commenced early after fast-track TKA. The primary outcome was the maximal distance walked in 6 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 51 publications
2
74
0
4
Order By: Relevance
“…During hospitalisation they are encouraged to be as active as possible, wearing their own clothes, participating in group physiotherapy and having their meals in a dining room together with other patients . We found that many participants were concerned about exercising and regaining muscular strength, as recent research recommend strength training and physical exercise soon after surgery . Physiotherapy sessions are supposed to start 2–3 weeks after surgery, but the majority of the participants in our study had already been in contact with a physiotherapist in their municipality before the interviews.…”
Section: Discussionmentioning
confidence: 93%
“…During hospitalisation they are encouraged to be as active as possible, wearing their own clothes, participating in group physiotherapy and having their meals in a dining room together with other patients . We found that many participants were concerned about exercising and regaining muscular strength, as recent research recommend strength training and physical exercise soon after surgery . Physiotherapy sessions are supposed to start 2–3 weeks after surgery, but the majority of the participants in our study had already been in contact with a physiotherapist in their municipality before the interviews.…”
Section: Discussionmentioning
confidence: 93%
“…This new approach to TKR was driven by several factors. First of all other specialties were ahead of orthopaedic surgery with regard to minimally invasive surgery principles [8]; second of all, the resurgence of UKR using mini-invasive approach gave surgeons the skills to transpose similar technique to TKR [98, 99]; third the development of computer-assisted technology with the navigation and robotic surgery which interestingly followed the progression of UKR growth on the market [12, 97]; and finally the rapid adoption of enhanced recovery thinking in arthroplasty surgery [61, 62]. …”
Section: Discussionmentioning
confidence: 99%
“…Modest changes to length of stay have impacted initial physical therapy approaches; however, there have not been significant shifts in specific treatment. Rehabilitation after TKA has not changed substantially in the past 7 years . Other unmeasured confounder or mediator variables might have influenced Patients' expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation after TKA has not changed substantially in the past 7 years. 32,33 Other unmeasured confounder or mediator variables might have influenced patients' expectations. Lastly, large variability in patient perceptions of time to functional recovery existed among particular activities, such as kneeling and being able to walk 5 blocks.…”
Section: Discussionmentioning
confidence: 99%